A tetrahedral DNA nanostructure-decorated electrochemical platform for simple and ultrasensitive EGFR genotyping of plasma ctDNA. Issue 13 (27th May 2020) - Wang, Xuyao; Wu, Jianping; Mao, Weilin; He, Xia; Ruan, Liming; Zhu, Junlan; Shu, Peng; Zhang, Zhenqi; Jiang, Bitao; Zhang, Xingguo
Abstract : In this study, we propose an on-site electrochemical platform for sensitive simultaneous genotyping of the two major EGFR mutations (19del and L858R) through plasma ctDNA based on tetrahedral DNA nanostructure decorated screen-printed electrodes. Abstract : Genotyping of the epidermal growth factor receptor (EGFR) mutation status is of great importance in the screening of appropriate patients with advanced non-small cell lung carcinoma (NSCLC) to receive superior tyrosine kinase inhibitor (TKIs) therapy. Yet conventional assays are generally costly with a relatively long turnaround time for obtaining results, which can lead to a bottleneck for immediately starting TKI therapy in late-staged patients. In this study, we propose an on-site electrochemical platform for sensitive simultaneous genotyping of the two major EGFR mutations (19del and L858R) through plasma ctDNA based on tetrahedral DNA nanostructure decorated screen-printed electrodes (SPE). Linear-after-the-exponential (LATE)-PCR combined with the amplification refractory mutation system (ARMS) was adopted to produce abundant biotin-labeled single-stranded DNA with high amplification efficiency and specificity. Disposable SPE decorated with self-assembled tetrahedral nanostructured DNA probes that showed ordered orientation and good target accessibility enabled the highly efficient hybridization of the specific amplicons through a sandwich-type and quantitatively translated the interfacial hybridization event into electrochemical signals via enzymatic amplification. Taking advantage of the ARMS-based LATE-PCR and the tetrahedral nanostructure-decorated SPE platform, we achieved the accurate detection of around 30 pg DNA of 19del or L858R, or as low as 0.1% of them in the presence of wild-type DNA. Moreover, the EGFR mutation profiles of 13 NSCLC patients we enlisted were accurately genotyped by our electrochemical platform, the results of which were in good agreement with those of commercial genetic detection methods.